2015
DOI: 10.1109/tip.2015.2417498
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Coding Unit Depth Decisions for Flexible Complexity Allocation in High Efficiency Video Coding

Abstract: In this paper, we propose a machine learning-based fast coding unit (CU) depth decision method for High Efficiency Video Coding (HEVC), which optimizes the complexity allocation at CU level with given rate-distortion (RD) cost constraints. First, we analyze quad-tree CU depth decision process in HEVC and model it as a three-level of hierarchical binary decision problem. Second, a flexible CU depth decision structure is presented, which allows the performances of each CU depth decision be smoothly transferred b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(84 citation statements)
references
References 22 publications
0
84
0
Order By: Relevance
“…Shen et al suggested a fast Bayesian theory based CU decision algorithm [36], where the sum of absolute transform differences (SATD), MV and RD costs were employed as the features. In [37], a three-output joint classifier was designed to control the risk of false prediction. In the machine learning based methods, almost all the information can be utilized to make the decision, such as the encoding parameters, intermediate values, spatio-temporal neighbouring blocks, texture complexities, and the performance of decision structure strongly relies on the selected features.…”
Section: Related Workmentioning
confidence: 99%
“…Shen et al suggested a fast Bayesian theory based CU decision algorithm [36], where the sum of absolute transform differences (SATD), MV and RD costs were employed as the features. In [37], a three-output joint classifier was designed to control the risk of false prediction. In the machine learning based methods, almost all the information can be utilized to make the decision, such as the encoding parameters, intermediate values, spatio-temporal neighbouring blocks, texture complexities, and the performance of decision structure strongly relies on the selected features.…”
Section: Related Workmentioning
confidence: 99%
“…SVM [28] has been used in fast inter mode decision for HEVC [29] [30]. In this subsection, we model the CU size decision as a binary classification problem.…”
Section: B Early Cu Split Decision Based On Linear Svmmentioning
confidence: 99%
“…In [41], the quad-tree CU depth decision process is modeled as a threelevel of hierarchical binary decision problem. In addition, a flexible CU depth decision structure is used to allow the performance of each CU depth decision be smoothly transferred between the coding complexity and RD performance along with binary classifiers to control the risk of false prediction.…”
Section: Related Workmentioning
confidence: 99%